التنمية والامن الإنساني في ظل اقتصاد السوق - محسن حسن, وسن (Journal of College of Education, 2020)
Many social and economical changes had occurred in the world since the eighteenth century until now, especially the crises experienced by the capitalist economic system, world war one and two, the victory over fascism, the changes that occurred in the third world, the defeat of the old colonial system, the emergence of the socialist system in the Soviet Union and some other socialist countries, as well as the cold war between the socialist and capitalist systems. In addition to that is the huge technological developments and globalization in all its fields.        All of these events influenced the economic thought and all the new economic theories were taken, all trying to work to get rid of the socialist and capitalist disadvantages, but take advantage of their positives as much as possible and apply these theories in capitalist countries. As for most socialist countries, led by the Soviet Union, they remained intransigent to their thoughts and weren’t able to take advantage of the scientific and intellectual developments in which they and the capitalist states had in its economic and market development which caused their failure and downfall, regardless of its positive intellectual and scientific impact on the people and nations of the world.       Again the speech about providing social welfare and the role of the government in that was brought back after the social disorders in some countries of the world, because of that, the developed countries sought to enable  them to be marginalized because they were deficient in composition and empowerment to overcome deprivation, and to create extensive and comprehensive change; these countries consider this to be part of their commitments to society and is one of the most important bases for achieving a better standard of living. Despite the utmost efforts of some countries to provide better means and facilities, but in some cases it may be narrowed to the point that it is merely a cash subsidy that is closer to the traditional concept of compassionate values and far from the concept of state welfare. This thesis includes three researches, the first one specializes in the history of social welfare in Iraq; the second research talks about human security in Iraq between state care and market fairs; the third research deals with the stage of structural adjustment and its implications for human security in Iraq.